Performance of the IBIS/Tyrer‐Cuzick model of breast cancer risk by race and ethnicity in the Women's Health Initiative. Issue 20 (6th July 2021) - Kurian, Allison W.; Hughes, Elisha; Simmons, Timothy; Bernhisel, Ryan; Probst, Braden; Meek, Stephanie; Caswell‐Jin, Jennifer L.; John, Esther M.; Lanchbury, Jerry S.; Slavin, Thomas P.; Wagner, Susanne; Gutin, Alexander; et al.
Abstract : BACKGROUND: The IBIS/Tyrer‐Cuzick model is used clinically to guide breast cancer screening and prevention, but was developed primarily in non‐Hispanic White women. Little is known about its long‐term performance in a racially/ethnically diverse population. METHODS: The Women's Health Initiative study enrolled postmenopausal women from 1993‐1998. Women were included who were aged <80 years at enrollment with no prior breast cancer or mastectomy and with data required for IBIS/Tyrer‐Cuzick calculation (weight; height; ages at menarche, first birth, and menopause; menopausal hormone therapy use; and family history of breast or ovarian cancer). Calibration was assessed by the ratio of observed breast cancer cases to the number expected by the IBIS/Tyrer‐Cuzick model (O/E; calculated as the sum of cumulative hazards). Differential discrimination was tested for by self‐reported race/ethnicity (non‐Hispanic White, non‐Hispanic Black, Hispanic, Asian or Pacific Islander, and American Indian or Alaskan Native) using Cox regression. Exploratory analyses, including simulation of a protective single‐nucleotide polymorphism (SNP), rs140068132 at 6q25, were performed. RESULTS: During follow‐up (median 18.9 years, maximum 23.4 years), 6783 breast cancer cases occurred among 90, 967 women. IBIS/Tyrer‐Cuzick was well calibrated overall (O/E ratio = 0.95; 95% CI, 0.93‐0.97) and in most racial/ethnic groups, but overestimated risk for Hispanic women (O/E ratio = 0.75; 95% CI, 0.62‐0.90). Discrimination did not differ by race/ethnicity. Exploratory simulation of the protective SNP suggested improved IBIS/Tyrer‐Cuzick calibration for Hispanic women (O/E ratio = 0.80; 95% CI, 0.66‐0.96). CONCLUSIONS: The IBIS/Tyrer‐Cuzick model is well calibrated for several racial/ethnic groups over 2 decades of follow‐up. Studies that incorporate genetic and other risk factors, particularly among Hispanic women, are essential to improve breast cancer–risk prediction. Abstract : The IBIS/Tyrer‐Cuzick model, which is used to guide clinical decision‐making about breast cancer prevention and screening, was found to perform well for most postmenopausal women in the Women's Health Initiative study. However, studies incorporating genetic and other risk factors, particularly for Hispanic women, should be prioritized to improve clinical breast cancer–risk prediction.